2021
DOI: 10.1097/scs.0000000000008196
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Cranial Measurements in Metopic Craniosynostosis/Trigonocephaly: Diagnostic Criteria, Classification of Severity and Indications for Surgery

Abstract: Metopic craniosynostosis is the second most frequent type of craniosynostosis. When the phenotypic presentation has been deemed severe the treatment is surgical in nature and is performed in infancy with fronto-orbital advancement and cranial vault remodeling. At the time of this writing, there is no consensus regarding an objective evaluation system for severity, diagnostic criteria, or indications for surgery. This study aims to review the anthropometric cranial measurements and the relative diagnostic crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 87 publications
1
11
0
Order By: Relevance
“…It is not possible with the presented sample to comment on the relative benefit or impact of different surgical techniques or the age of surgery. Further, informed comments on the impact of preoperative severity owing to a lack of clear consensus for the definition of clinical severity in MS are not feasible 46 . The absence of such a clear methodology for defining severity would preclude a robust and meaningful analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not possible with the presented sample to comment on the relative benefit or impact of different surgical techniques or the age of surgery. Further, informed comments on the impact of preoperative severity owing to a lack of clear consensus for the definition of clinical severity in MS are not feasible 46 . The absence of such a clear methodology for defining severity would preclude a robust and meaningful analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Further, informed comments on the impact of preoperative severity owing to a lack of clear consensus for the definition of clinical severity in MS are not feasible. 46 The absence of such a clear methodology for defining severity would preclude a robust and meaningful analysis. The impact of differing surgical techniques, and timing of surgical intervention, on psychological outcomes is poorly understood within the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In both studies, the cut-off point to determine surgical indication remained subjective, and poor consensus for the intermediate presentation of metopic craniosynostosis was found. In addition, Sisti et al 5 recently reviewed all literature in PubMed on trigonocephaly, relating to 15 anthropometric cranial measurements for surgical indications. They found that most articles have a lack of diagnostic criteria for trigonocephaly.…”
Section: Reply: Cerebral Blood Flow Of the Frontal Lobe In Untreated ...mentioning
confidence: 99%
“…To assess the severity of metopic synostosis, several measures have been described previously. These include anthropometric measures on CT scans such as the interfrontal angle (angle between bilateral pterion to nasion lines), the amount of frontal stenosis (interparietal distance / intercoronal distance), and the recently developed quantitative shape severity score, as well as measures acquired through 3D imaging systems 2–9 . However, CT scans require radiation exposure and are consequently rarely repeated postoperatively, and consensus on what constitutes the best anthropometric measure is lacking 8 .…”
mentioning
confidence: 99%
“…These include anthropometric measures on CT scans such as the interfrontal angle (angle between bilateral pterion to nasion lines), the amount of frontal stenosis (interparietal distance / intercoronal distance), and the recently developed quantitative shape severity score, as well as measures acquired through 3D imaging systems. [2][3][4][5][6][7][8][9] However, CT scans require radiation exposure and are consequently rarely repeated postoperatively, and consensus on what constitutes the best anthropometric measure is lacking. 8 3D imaging systems are not easily accessible for all health care providers as they require expensive equipment and expertise in analyses of data obtained.…”
mentioning
confidence: 99%